Analisis Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen Melalui Aplikasi Online Start-Up Di Kota Medan - suharman, suharman (Universitas Sam Ratulangi, 2019)
This study aims to determine the factors that can influence consumer purchasing decisions in the Start-Up E-commerce application. The development of information technology continues to increase rapidly, including the e-commerce industry with many emerging start-up applications in Indonesia. The results of this study are the formation of five new factors namely Practical Factors, Comfort Factors, Buyer Characteristic Factors of Perception of Risk, and Product Availability Factors as needed. These factors can be a consideration for consumers in deciding on product purchases through the online Start-up applicationKeywords: Purchase Decision, Online Application, Start-up